Visualizing capability and stability on a single chart. Issue 4 (2nd October 2017) - Braun, W. John; Han, Lengyi
Abstract: Clear and simple data visualization is critical when communicating information about a process to less technically oriented personnel. This paper demonstrates that process stability and capability can be conveyed on one plot. Since, location and scale are not the only features of the process that might change when the process leaves control, we consider simple charts that can detect such changes in addition to location and scale. A simulation study demonstrates when and where various control charts might be best at detecting particular out of control conditions. The meaning behind conventional capability indices can be quickly inferred from the proposed tool. The visualization tool is demonstrated on three data-sets.